Did the 2007 Legal Arizona Workers Act Reduce the State's Unauthorized Immigrant Population? - Bohn, Sarah; Lofstrom, Magnus; Raphael, Steven (The Review of Economics and Statistics, 2014)
We test for an effect of Arizona's 2007 Legal Arizona Workers Act (LAWA) on the proportion of the state's population characterized as noncitizen Hispanic. We use the synthetic control method to select a group of states against which Arizona's population trends can be compared. We document a notable and statistically significant reduction in the proportion of the Hispanic noncitizen population in Arizona. The decline observed matches the timing of LAWA's implementation, deviates from the time series for the synthetic control group, and stands out relative to the distribution of placebo estimates for other states in the nation.